Evaluation of risk factors for and subsequent mortality from poor graft function (PGF) post allogeneic stem cell transplantation. Issue 6 (12th May 2021) - Prabahran, Ashvind; Koldej, Rachel; Chee, Lynette; Wong, Eric; Ritchie, David
Abstract: Poor Graft Function (PGF) is defined by multi-lineage cytopenias with complete donor chimerism post allogeneic transplantation, Risk factors for and subsequent mortality from PGF were assessed in our transplant cohort. Non-sibling donor [OR 1.97; 95% CI 1.02–3.70], ICU admission [OR 5.28; 95% CI 2.29–11.88] or blood culture positivity within the first 30 days [OR 1.67; 95% CI 1.07–2.62], grade III–IV acute graft vs host disease (GVHD) [OR 4.082; 95% CI 2.31–7.16] and CMV viremia [OR 2.43; 95% CI 1.53–3.88] and were significantly associated with development of PGF. PGF patients without count recovery had a 2 year OS of 6%. Severe GVHD, thrombocytopenia and anemia portended inferior survival and were used to develop a prognostic score for mortality from PGF. This analysis identifies risk factors predictive of PGF and poor survival in those without recovery.